Towards the development of Agrobacterium tumefaciens and particle bombardment-mediated cassava transformation - Sarria, Rodrigo A.; Gómez, A.; Cataño C, ML; Herrera, P.V.; Calderón, A.; Mayer, Jorge Edgard; Roca, W. (International Center for Tropical Agriculture, 1993)
Our strategy for Aqrobacterium-mediated cassava transformation involves the utilization of cotyledonary leaves from somatic embryos and infection with both wild and disarmed strains. Virulence tests for wild Aqrobacterium strains as well as regeneration protocols have been developed; the plasmid used in all the experiments was the pGV 1040 containing the uid A, the bar and the npt ll genes (provided by Plant Genetic Systems. Gent). Sensitivity levels of cassava tissues to the commercial herbicide Basta, used as selection agent, were determined. Minimum lethal doses for the herbicide were 1 mg/l for immature leaves and 18 mg/l for somatic embryos. Results with kanamycin as selection agent were inconsistent. Only somatic embryos showed endogenous uid A gene expression; endogenous activity was reduced by 70-80 using the Kosugi protocol (1990), which includes methanol. Expression of opine synthesis genes of a wild Aqrobacterium strain, isolated from cassava tumors, was obtained after transformation of cotyledonary leaves of somatic embryos with the wild strain. Transformation experiments are now under way using the wild Aqrobacterium strain carrying the pGV 1040 plasmid. A biolistic device was used to bombard early stage somatic embryos using the pGV 1040 construct harboring the same genes as in the Aqrobacterium experiments. An average of 20 GUS expressing spots per 0,5 cm2 of embryogenic tissue was obtained. GUS expression in proliferating somatic embryos has been observed after one and two months from bombardment.